Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12944-019-0960-4
|View full text |Cite
|
Sign up to set email alerts
|

Irisin interaction with adipose tissue secretions by exercise training and flaxseed oil supplement

Abstract: BackgroundPrevious studies have shown that physical training and natural diet able to change the expression and concentration of peptides and proteins. Myokines and adipokines play an important role in metabolism and metabolic syndrome. Therefore, the purpose of the present study was to investigate the effect of high-intensity interval training (HIIT) and supplementation of flaxseed oil on plasma irisin, nesfatin-1 and resistin in male rats.MethodsForty adult male rats were randomly divided into four groups (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
(48 reference statements)
0
18
0
1
Order By: Relevance
“…Once converted from white to brown, adipose tissue takes on the function of dispersing heat energy, while white adipose tissue is responsible for storing energy. This event, in turn, causes an increase in total body energy expenditure [32].…”
Section: Discussionmentioning
confidence: 99%
“…Once converted from white to brown, adipose tissue takes on the function of dispersing heat energy, while white adipose tissue is responsible for storing energy. This event, in turn, causes an increase in total body energy expenditure [32].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the design of many studies increasing the concentration of Nesfatin-1 in the body is based on direct injection in the brain. Hossein Shirvani et al [65] found that exercise or supplementation of flaxseed oil could also increase the level of Nesfatin-1 in the body, which reduces the food intake through calcium signaling pathways, thereby decreasing the occurrence of obesity. Aside from regulating food intake, many researchers started to focus on the relationship between brown adipose and Nesfatin-1.…”
Section: The Nervous System Regulates the Occurrence Of Obesity Thmentioning
confidence: 99%
“…Exercise-activated mitophagy was mediated by the irisin/FNDC5-PINK1/Parkin-LC3/P62 pathway, which could significantly increase the level of myocardial anti-oxidation and improve cardiac function [ 13 ]. As the myogenic exerkine [ 8 ], irisin could result in clearer cardioprotection by exercise training [ 14 , 15 ], However, whether this protective effect works through PINK1/Parkin-mediated mitophagy still lacks experimental evidence. Furthermore, whether the cardioprotective effect of exercise also works through this mechanism and which exercise mode is better in MI myocardium still remain to be studied.…”
Section: Introductionmentioning
confidence: 99%